Building information modeling in construction conflict management - Charehzehi, A.; Chai, C.; Md Yusof, A.; Chong, Heap Yih; Loo, S. (SAGE PUBLICATIONS INC, 2017)
Dispute is recognized as critical cause of deficiency and low performance in construction projects. Plenty of studies have been done in construction dispute management recently; however, there are no studies on construction dispute elimination. This study aims to propose a building information modeling (BIM) approach to control conflict causes before the occurrenc e of dispute. BIM is one of the latest platforms that promote a high level of collaboration, information sharing, and coordination where its implementation ranges from project initialization to completion stage. The circumstances associating with BIM technology can be utilized to explore the possibilities in conflict and dispute resolution system. Questionnaire surveys are used to collect the primary data. Analytical hierarchy process (AHP) and multi attribute utility technique (MAUT) are adopted to develop an algorithm and a decision-making framework to manage and resolve the potential conflict causes, particularly for the Malaysian construction industry. Data analysis emerged that five critical conflict factors in Malaysian construction industry are insufficient monitoring of CPM scheduling and updates requirements; failures to understand and correctly bid or price the works; delay in running bill payment; inadequate contractors’ management, supervision, and coordination; and error and omission in design that are originated from time, cost, quality, and documentation. Further analysis to prioritize BIM functions in construction conflict management has been done by the combination of AHP and MAUT results. Consequently, it is affirmed that clash detection and cost estimating, 4D scheduling, 3D visualization and structure analysis as BIM functions obtained the highest score to control conflicting factors.